Potensi Aktivitas Antidiabetes Berbagai Jenis dan Varian Tanaman Mangga (Mangifera spp.) - Agnes Monica Murisla; Zulpakor Oktoba; Femmy Andrifianie; Ramadhan Triyandi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Diabetes mellitus is a chronic disease with a significantly increasing global prevalence, especially in developing countries. Current treatments use synthetic antidiabetic drugs that are generally expensive and have various side effects. This study aims to examine the potential of mango plants (Mangifera spp.) as antidiabetic agents through a systematic literature review. Literature searches were conducted through the electronic databases PubMed and Google Scholar using the keywords "Mangifera/mango" and "antidiabetic". From the search results, 25 relevant articles were obtained for further review, consisting of 15 articles on in vitro testing and 10 articles on in vivo testing. The search results identified 17 mango plant variants worldwide that have been shown to have antidiabetic activity. Each mango species has unique characteristics and different nutritional content and bioactive compounds. Various parts of the mango plant, including leaves, fruits, seeds, and bark, contain bioactive compounds such as flavonoids, tannins, saponins, and terpenoids. These compounds contribute to antidiabetic activity through several mechanisms, namely inhibition of α-glucosidase and α-amylase enzymes, increased insulin sensitivity, and reduced blood glucose levels. Mango plant secondary metabolites are not only effective, but also have the potential to be an alternative antidiabetic treatment that is more affordable and safe compared to synthetic drugs. It can be concluded that Mangifera spp. has great potential to be developed as an innovative diabetes therapy. Further research through clinical trials is needed to confirm its effectiveness as an antidiabetic agent.